COLLAGEN FIBERS AND PROTEOGLYCANS IN THE GLIAL SCAR IN THE BRAIN AFTER HEMORRHAGIC STROKE AND UNDER CONDITIONS OF MODULATION OF COMPENSATORY-REPAIR PROCESSES - Grabovyi, O.M.; Mervinsky, T.S.; Savosko S.І.; Yaremenko, L.M. (World of Medicine and Biology, 2025)
In the case of a stroke, a glial scar forms around the affected area. According to the hypothesis, scar formation occurs not only by glial cells but also mesenchymal cells, which should be reflected in the cellular composition and extracellular matrix. The aim of this study was to investigate changes in collagen and proteoglycans content in the glial scar in the brain after hemorrhagic stroke and under conditions of modulation of compensatory-repair processes. A local hemorrhagic stroke was modeled in rats, and histochemical methods were used to study changes in collagen and proteoglycans content in the scar formation areas. An increase in collagen accumulation was observed on days 3, 10, and 30 after the stroke, with a tendency to decrease by day 60. The elimination of the hemorrhage was characterized by the accumulation of macrophages with PAS-positive cytoplasm and an increase in proteoglycans content around the hemorrhage. This indicates the involvement of mesenchymal-derived cellular elements in scar formation. In conditions of granulocyte-colony stimulating factor application, collagen accumulation was significantly lower, as it was with dexamethasone treatment, while isolated dexamethasone action led to scar formation characterized by an increase in collagen and macrophage content.